A discrepancy in logistics and supply chain management: Findings from national iron plus initiative process documentation in Odisha - Vikas Bhatia; Swayam Pragyan Parida; Preetam B Mahajan; Sarika Palepu; Sourabh Paul (Wolters Kluwer Medknow Publications, 2020)
Introduction: Anemia is highly prevalent in India affecting all age groups. In 2016, process documentation program was done in Odisha by Department of Health and family Welfare, Government of Odisha with the aid of UNICEF and All India Institute of Medical Sciences, Bhubaneswar to assess National Iron Plus Initiative program. The objectives were to assess facilitating factors and hindrances in implementation of program. In the present study, hurdles in logistics and supply chain management are discussed. Material and Methods: A mixed-methods study was done among four districts (3 poor performing and one good performing) based on Iron folic acid tablets consumption. Two blocks from Keonjhar and Jagatsinghpur and one block from Bhadrak and Kalahandi were selected. In depth interviews and Focus group discussion were done among 170 respondents (officials and beneficiaries). By probability proportion to size, 50 sub-centres were chosen and front line workers interviewed. Data was collected by survey team and analysis was done using Nvivo qualitative research software program for qualitative surveys and Microsoft Excel for quantitative surveys. Results: It was seen that there were discrepancies in the method (bypassing officials), frequency of indenting (quarterly, bi-annual and annual), supply chain, stock out management (informal methods) and flow of supply (prolonged quarantine period). It was also seen that only 41% of sub-centres had IFA tablets at the time of survey. Conclusion: Logistics and supply chain management play a crucial role in the success of any program. Timely and orderly management, centralised method and formal approach need to be incorporated.